Ethanol 50% as Antidote in Propylene Glycol Due to Antifreeze Ingestion in General Hospital, Bali, Indonesia: Case Report - Morris Lintong Barimbing; I Gde Raka Widiana (PERNEFRI (PERHIMPUNAN NEFROLOGI INDONESIA), 2025)
Propylene glycol intoxication is a medical emergency requiring immediate intervention. It is metabolized by alcohol dehydrogenase into toxic metabolites, such as lactate and pyruvate, which can lead to metabolic acidosis and organ failure. The primary antidote strategy involves inhibiting alcohol dehydrogenase to prevent the formation of these harmful metabolites. This case report highlights a 53-year-old man who accidentally ingested a propylene glycol radiator coolant. He presented with symptoms of nausea, vomiting, and metabolic acidosis, confirmed through laboratory tests. With no fomepizole available—the preferred antidote—the patient was administered ethanol (gin) at a concentration of 50% over 10 minutes until intoxication occurred. Ethanol competes with propylene glycol for alcohol dehydrogenase, thereby preventing the formation of toxic lactate metabolites. The patient recovered without complications after two days of being given oral ethanol and was discharged. Although ethanol use as an antidote for propylene glycol poisoning is limited, this case underscores its potential effectiveness in reducing morbidity and mortality when fomepizole is unavailable. This approach demonstrates the importance of timely intervention in cases of toxic alcohol exposure.